High wage workers and low wage firms : negative assortative matching or statistical artefact? - Martyn J. Andrews; Len Gill; Thorsten Schank; Richard Upward (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2006)
In the empirical literature on the estimation of firm and worker heterogeneity using linked employer-employee data, unobserved worker quality appears to be negatively correlated with unobserved firm quality. We investigate the possibility that this is simply caused by standard estimation error and develop formulae that show that the estimated correlation is biased downwards if there is true positive assortative matching and when any conditioning covariates are uncorrelated with the firm and worker fixed effects. This result applies to any two-way (or higher) error-components model estimated by fixed-effects methods. We apply these bias corrections to a large German linked employer-employee dataset. We find that although the biases can be considerable, they are not sufficiently large to remove the negative correlation entirely. – – Auf der Basis von zusammengefügten Betriebs- und Personendaten findet sich in der empirischen Literatur eine negative Korrelation zwischen den unbeobachteten Eigenschaften von Beschäftigten und denen von Betrieben. Wir zeigen formal, dass die geschätzte Korrelation nach unten verzerrt ist, sofern ein positives Matching existiert und sofern die übrigen Kovariate mit den Betriebs- und Beschäftigten Fixed Effects unkorreliert sind. Dieses Ergebnis kann allgemein auf jedes mehrdimensionale Fixed Effects Modell übertragen werden. Für kombinierte Firmen-Beschäftigtendaten aus Deutschland finden wir eine beträchtliche Verzerrung in der geschätzten Korrelation. Diese ist jedoch nicht groß genug, um die ermittelte negative Korrelation vollständig erklären zu können.
Keywords: J30; C87; C23; 330; linked employee-employer panel data; biases; fixed-effects